2022
DOI: 10.3390/ijms231810368
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Antitumor Activities of Cellular Immunotherapy with CIK Lymphocytes and Interferons against KIT/PDGFRA Wild Type GIST

Abstract: Gastrointestinal stromal tumors (GISTs) are rare, mesenchymal tumors of the gastrointestinal tract, characterized by either KIT or PDGFRA mutation in about 85% of cases. KIT/PDGFRA wild type gastrointestinal stromal tumors (wtGIST) account for the remaining 15% of GIST and represent an unmet medical need: their prevalence and potential medical vulnerabilities are not completely defined, and effective therapeutic strategies are still lacking. In this study we set a patient-derived preclinical model of wtGIST to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“…CIK cells were successfully generated and proliferated in vitro to achieve a CIK cell [ 27 ] percentage that yielded a CD3 + CD56 + value of 46% ( Figure 6A ). To assess the effect of CIK cells in the AGE microenvironment, we used a CCK-8 assay to analyze the performance of HUVECs and fibroblasts indirectly co-cultured with CIK cells.…”
Section: Resultsmentioning
confidence: 99%
“…CIK cells were successfully generated and proliferated in vitro to achieve a CIK cell [ 27 ] percentage that yielded a CD3 + CD56 + value of 46% ( Figure 6A ). To assess the effect of CIK cells in the AGE microenvironment, we used a CCK-8 assay to analyze the performance of HUVECs and fibroblasts indirectly co-cultured with CIK cells.…”
Section: Resultsmentioning
confidence: 99%
“…The killing effect of CIK cells on tumors is characterized by high efficiency and lack of major histocompatibility complex (MHC) restriction [17]. CIK cells have good synergistic effects with other adjuvant therapies and the advantages of strong antitumor activity, wide antitumor spectrum, and no obvious adverse reactions [18][19][20]. Studies have shown that adaptive therapy with CIK cells is currently the best cellular-immunotherapy regimen for solid tumors and has a good therapeutic effect on a variety of tumors, especially liver cancer and leukemia [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Several stromal or intracellular mechanisms implicated in the synergistic activity have been identified. As mentioned above cytokines and cytotoxic agents improve immunemediated cell killing through TME modulation not only by decreasing the ratio of Tregs, but also by induction of a memory effector cell response (102,104) or direct anti-tumor effect by blockade of cytokine-receptors (105). Co-incubation with dendritic cells has yielded a higher percentage of CD3, CD4 (+) helper T and CD8 (+) T cell accumulation in cell cultures, resulting in improved antiproliferative and cytotoxic effects not only through induction of immune-mediated cell killing, but also direct activation of CIK cells through CCR5 signaling (115,116).…”
Section: Combined Immunotherapy Approaches: Rationale and Preclinical...mentioning
confidence: 99%
“…Favorable outcomes achieved with CIK cell therapy led to increased efforts to improve efficacy with combined approaches. There exists strong preclinical evidence on the synergistic efficacy of proinflammatory cytokines such as interleukins (101)(102)(103)(104) and interferon (105) as well as cytotoxic agents (106), novel small molecule inhibitors (107)(108)(109), immune checkpoint inhibitors (110)(111)(112), monoclonal antibodies (113,114) and dendritic cell (115)(116)(117) or viral-based vaccines (118-120) combined with adoptive cell therapy. Several stromal or intracellular mechanisms implicated in the synergistic activity have been identified.…”
Section: Combined Immunotherapy Approaches: Rationale and Preclinical...mentioning
confidence: 99%